Hubungan Iklim Keselamatan dengan Kekerasan di Tempat Kerja pada Perawat di Rumah Sakit Pemerintah Provinsi Aceh - Habibi, Habibi; Maliki, Imam; Faidhil, Faidhil (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
This study aims to explore the relationship between overtime and workplace violence (WPV) against nurses in the Government Hospital of Aceh Province. The research method employed is quantitative with a cross-sectional design. Data were collected from RSUD Aceh during the period of May 31 to June 14, 2022. Out of 161 respondents, 127 nurses successfully participated, resulting in a response rate of 78.9%. Sampling was conducted using a total sampling technique, involving nurses working in the emergency room, pediatric ward, pediatric surgery ward, male internal medicine ward, and internal medicine ward at the Government Hospital of Aceh Province. Data analysis was performed using univariate and bivariate approaches. The study found a significant relationship between overtime and psychological violence against nurses in RSUD Aceh (p=0.000). However, no significant relationship was found between physical violence among nurses at RSUD Aceh (p=0.290). In conclusion, overtime work is associated with the occurrence of psychological/non-physical violence against nurses working in the Government Hospital of Aceh Province. Keywords: WPV, Overtime, Nursing